Design and functional evaluation of an adjustable powered exoskeleton for gait assistance. - Oyama, Hideki; Ikeda, Hiroyasu (Technology & Disability, 2025)
Background: Exoskeleton technology supports gait rehabilitation in individuals with spinal cord injury (SCI), promoting walking independence. However, current powered exoskeletons often face challenges in adaptability, particularly skin problems caused by inadequate fit to the lower limbs. Objective: This study aimed to develop a powered exoskeleton for SCI featuring a unique mechanism to adjust the left-right joint angle, accommodating diverse lower limb alignments. Functional evaluation included fitting (device-to-body clearance, subjective pain, discomfort, and fit) and kinematic (hip and knee joint angles) parameters using markerless motion capture. Methods: A comparative study was conducted to compare walking with and without a prototype. Results: Ten healthy adults (seven males, three females; average height, 167 ± 10 cm; weight, 58 ± 9 kg) participated in the study. Clearance values were acceptable, pain and discomfort were minimal, and fit satisfaction was high. Gait analysis revealed significant positive correlations between normal walking and using the prototype for both joint angles (hip: r = 0.70, p < 0.001; knee: r = 0.84, p < 0.001), indicating effective gait assistance. Conclusions: A prototype exoskeleton with adjustable mechanism was developed, fitting well and effectively assisting with walking. Further refinement and testing with SCI patients are necessary for its clinical application.